Research of Economical Shift Rule of Automatic Power Shift Transmission of Tractor - Xi Zhiqiang; Zhou Zhili; Zhang Mingzhu (Jixie chuandong)
When working at light load operation（ such as sowing,weeding,transplanting,harvesting,etc.）,the traditional tractor has the problem of low power utilization ratio and high fuel consumption. Through analyzing the best economy index and its influence factors of tractor,a kind of economical shift rule is put forward,which based on the minimum fuel consumption rate of tractor. It requires not only the operating point of the engine located at the lowest fuel consumption zone,also need the tractor traction efficiency to be higher. For this reason,the slip rate of driving wheel is introduced to constitute economical shift rule and its control strategy,which takes the speed,drive wheel speed,engine speed,throttle opening and transmission gear ratio of tractor as control parameters. The fuzzy control is used to identify the driving intention,and the driver intervention on the shifting process is introduced to the transmission control,which can reflect the actual working environment of the tractor. Taking the YTO LA2004 wheeled tractor which equipped with automatic power shift transmission as investigative subject,the simulation analysis of light load working condition is carried out. The results show that the gear and throttle opening change with traction load,which ensure that the working point of the engine is in a low fuel consumption zone. The fuel consumption rate of tractor is reduced and the stability of the actual speed of the tractor is achieved. A theoretical basis for the development of automatic transmission control system of tractor is provided by the research.